2014
DOI: 10.7150/jca.7048
|View full text |Cite
|
Sign up to set email alerts
|

Future Directions for Monitoring Treatment Responses in Breast Cancer

Abstract: In the prior review, we outlined the current standard of care for monitoring treatment responses in breast cancer and discussed the many challenges associated with these strategies. We described the challenges faced in common clinical settings such as the adjuvant setting, neoadjuvant setting, and the metastatic setting. In this review, we will expand upon future directions meant to overcome several of these current challenges. We will also explore several new and promising methods under investigation to enhan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
4
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…Articles contributed by George E. Peoples' group have concluded that there are several opportunities to improve how we monitor response to breast cancer treatment 5 , 6 . Only by understanding the current standard of practice regarding all aspects of treatment can we begin to advance the field in a meaningful way.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…Articles contributed by George E. Peoples' group have concluded that there are several opportunities to improve how we monitor response to breast cancer treatment 5 , 6 . Only by understanding the current standard of practice regarding all aspects of treatment can we begin to advance the field in a meaningful way.…”
mentioning
confidence: 99%
“…Several fields of cancer care including surgical, radiation and medical oncology, pathology, and radiology work together within integrated practice units to ensure proper study design, selection and coordination of care. They sought to provide a broad overview of these various fields of cancer care, and we believe that future real-world and nimble clinical trials will need to be performed in various clinical pathways discussed in order to provide more granularity and an accelerated pace of discovery for breast cancer researchers 5 , 6 . The current paradigm of first testing new techniques or technologies in the metastatic setting prior to implementation in the adjuvant setting has been challenged by researchers who are committed to accelerating the speed of progress in breast cancer research.…”
mentioning
confidence: 99%
See 2 more Smart Citations